Parahita Audit Information System Based On COBIT 4.1 Parahita Diagnostic Center - Naufal Alif Syahlawal Akbar; Haryanto Tanuwijaya; Erwin Sutomo (Jurnal Sistem Informasi Universitas Dinamika, 2017)
Parahita Diagnostic Center is a laboratorium company in Dharmawangsa number 66 and 70 Surabaya. Parahita has applied infromation technology which integrated and centralized to increase the customer satisfaction and service quality that is called Parahita Information Systems (PARIS). However, the problem in the application of PARIS is no transaction data saving overall and some time difference result between the output and input in the application. So far, the root of the problem is unrecognized. Information System Audit which refers to COBIT 4.1 audit standard is applied to overcome the problem. COBIT 4.1 audit applies ISACA audit steps. The steps are preparation, planning, implementation and report. The types of audit are financial and customer perspectives. The financial perspective consist of two aims of business, eight aims of TI and twenty processes of TI. The customer perspective consists of four aims of business, thirteen aims of TI and twenty three processes of TI. The result of information system audit application has 3,63 in financial perspective. It can be called as Defined which means information system activities in the company as standard work procedures and communicate through formal activities. In addition, it is found the invention and reccomandation for improvement and development system.